Technologies of man-made placer development in active and closed waste storages - Medvedeva, O.A. (Геотехнічна механіка, 2015)
The article describes a technology for valuable components extracting from the man-made waste storages at the Krivbass ore-dressing and processing enterprises which are considered as promising man-made placers. Two approaches to such placers developing are considered which assume valuable component extraction both after closing and in process of operation of the waste storages. It is shown that implementation of practice of valuable components co-extraction from areas between dam and pond in conjunction with technology of combined waste storing requires changing of technological scheme in the maps of inwash district, and, to this end, it is rational to combine several operations. Technological parameters of the co-extraction from the man-made placers by means of hydromechanical facilities were grounded. The required performance of hydrotransport facilities needed for delivering tailings to the current inwash horizon and concentration of the discharged pulp were specified. В роботі запропоновані технології видобутку корисних копалин з сховищ відходів збагачення ГЗКів Кривбасу, які розглядаються як перспективні техногенні родовища. Розглянуто два підходи до розробки таких родовищ, які припускають видобуток техногенних розсипів як після закриття сховища відходів, так і в процесі його експлуатації. Показано, що впровадження супутнього видобутку цінного компонента з придамбових ділянок пляжу спільно з технологією комбінованого складування відходів вимагає зміни технологічної схеми карт ділянки намиву, що раціонально зробити, об'єднавши виконання декількох операцій. Обґрунтовано параметри технології супутнього видобування техногенних розсипів з використанням засобів гідромеханізації. Встановлена необхідна продуктивність гідротранспортних установок, що забезпечують відведення відходів збагачення на поточний ярус намиву, а також концентрації пульпи, яка відводиться. В работе предложены технологии добычи полезных ископаемых из хранилищ отходов обогащения ГОКов Кривбасса, которые рассматриваются как перспективные техногенные месторождения. Рассмотрены два подхода к разработке таких месторождений, которые предполагают добычу техногенных россыпей как после закрытия хранилища отходов, так и в процессе его эксплуатации. Показано, что внедрение попутной добычи ценного компонента с придамбовых участков пляжа совместно с технологией комбинированного складирования отходов требует изменения технологической схема карт участка намыва, что рационально сделать, объединив выполнения нескольких операций. Обоснованы параметры технологии попутной добычи техногенных россыпей с использованием средств гидромеханизации. Установлена необходимая производительность гидротранспортных установок, обеспечивающих отведение отходов обогащения на текущий ярус намыва, а также концентрации отводимой пульпы.